Eksplorasi hubungan emotional exhaustion dan work culture pada teacher performance - Ratnasari, Ina (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2021)
This study aims to explore the effect of emotional exhaustion and work culture on teacher performance. In this study, using a proportional random sampling technique and a sample of 69 teachers who were then directed to fill out the research questionnaire. The analysis technique used is multiple linear regression with data processing using SPSS version 22 statistics. Based on the results of data analysis, it was found that the t-test t value was significant for the emotional exhaustion variable of t = 0.006 <0.05. Thus emotional exhaustion has a significant effect on teacher performance. And the significant value for work culture is t = 0.000 <0.05. Thus work culture has a significant influence on teacher performance. While the test results using the F test can be said that all independent variables (emotional exhaustion, and work culture) simultaneously affect teacher performance. This can be seen from the significant level of F, which is 0.000 <0.05.